Funding Management Training to Improve Service Quality Education in Thammsat Wittaya Thailand - Rahmayati Rahmayati; Ade Gunawan (CERED Indonesia Institute, 2020)
Devotion public This intends to see the real phenomenon of implementation of management financing For Increase Quality Service Education in Thammsat Wittaya Thailand. The purpose of this research is to: (1) get a description of the activities education financing planning ( budgeting ), (2) implementation of education financing ( actuating ), (3) supervision of education financing ( controlling ) at Thammsat Wittaya Thailand. From results devotion community obtained findings as following: First, planning financing education ( budgeting ) is process prepare a series of decisions to take action described in a real concept for carrying out the life of the future madrasa with adequate financing programmed to achieve goals and produce ideal designs, planning results form efficiency budget, maximization function management And need student accommodated.